Electronic Structure of a Self-Assembled Monolayer with Two Surface Anchors: 6-Mercaptopurine on Au(111) - Fernández, Cynthia Carolina (2018)
The electronic structure of aromatic and aliphatic thiols on Au(111) has been extensively studied in relation to possible applications in molecular electronics. In this work, the effect on the electronic structure of an additional anchor to the S-Au bond using 6-mercaptopurine as a model system has been investigated. Results from X-ray photoelectron spectroscopy, near-edge X-ray absorption fine structure spectroscopy, and density functional theory (DFT) confirm that this molecule adsorbs on Au(111) with S-Au and iminic N-Au bonds. Combined ultraviolet photoelectron spectroscopy and DFT data reveal that formation of the 6MP self-assembled monolayer generates a molecular dipole perpendicular to the surface, with negative charges residing at the metal/monolayer interface and positive charges at the monolayer/vacuum interface, which lowers the substrate work function. Scanning tunneling microscopy shows two surface molecular domains: a well-ordered rectangular lattice where molecules are tilted on average 30° with respect to the substrate and aligned 6MP islands where molecules are standing upright. Finally, we found a new electronic state located at -1.7 eV with respect to the Fermi level that corresponds to a localized π molecular state, while the state corresponding to the N-Au bond is hybridized with Au d electrons and stabilized at much lower energies (-3 eV).